The Existence of Fixed Points for a Different Type of Contractions on Partial b-Metric Spaces - Muhammad Nazam; Hüseyin Işik; Khalil Javed; Muhammad Naeem; Muhammad Arshad (Journal of Mathematics)
The aim of this study is to present fixed point results in the setting of partial b-metric spaces. A different type of contractions is used to prove fixed point results in the given space, which are real generalization of many well-known results. The readers are also provided with some very interesting examples to illustrate the feasibility of the proposed work.